2019
DOI: 10.5296/ber.v9i2.14756
|View full text |Cite
|
Sign up to set email alerts
|

Ascendants That Influence the Adoption of E-government Services among Citizen of Pakistan

Abstract: In this research study, the author seeks to discover the predecessors of e-government services adoption among the citizen of Pakistan. To study the e-government adoption, researcher integrates extended TAM and theory of planned behaviour. Cross-sectional research technique was used and in total data was collected from 240 citizens of Pakistan. Results depict that facilitating conditions, performance expectancy, effort expectancy positively impact the citizen attitude towards adoption of e-government facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
3
1
Order By: Relevance
“…Our results have indicated that PE, effort expectancy, and social influence do not have a positive impact on the attitude. These findings are a departure and different from studies that demonstrated that PE and effort expectancy are both significant predictors of the attitudes toward the adoption of egovernment services (Dwivedi et al, 2017;Hammad et al, 2019). Although our findings are inconsistent with the findings of Verkijika & De Wet, 2018 that PE predicts attitude, it is, however, consistent with the same study that showed that effort expectancy does do not predict the attitudes toward the adoption of egovern ment services.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results have indicated that PE, effort expectancy, and social influence do not have a positive impact on the attitude. These findings are a departure and different from studies that demonstrated that PE and effort expectancy are both significant predictors of the attitudes toward the adoption of egovernment services (Dwivedi et al, 2017;Hammad et al, 2019). Although our findings are inconsistent with the findings of Verkijika & De Wet, 2018 that PE predicts attitude, it is, however, consistent with the same study that showed that effort expectancy does do not predict the attitudes toward the adoption of egovern ment services.…”
Section: Discussioncontrasting
confidence: 99%
“…Considering the other models utilized in e-Government acceptance and use other than UTAUT, it is seen that, generally, Technology Acceptance Model-TAM is preferred (Çabuk et al, 2017; Lin et al, 2011; Mensah et al, 2017, 2018), and in some studies, TAM and Diffusion of Innovation–DOI’nin (Carter & Bélanger, 2005) or TAM and Theory of Planned Behavior–TPB’nin (Hammad et al, 2019) are unified and used. However, in some studies, on the other hand, it is seen that only Social Cognitive Theory-SCT (Zhao et al, 2019), Theory of Planned Behavior-TPB (Azamela et al, 2022) or Unified Model of Electronic Government Adoption–UMEGA, which is an extension of Unified Theory of Acceptance and Use of Technology-UTAUT (Mensah et al, 2020; Verkijika & De Wet, 2018) is preferred.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The factors necessary for the success of e-Government are development, management, institutional structure, technical infrastructure, human infrastructure and e-Government portal (S. Demir, 2019;Naralan, 2010;Y€ ur€ uk & O ¨ztas x, 2017). There are many studies in the literature to determine the acceptance and use of the e-Government system (Azamela et al, 2022;Bhuasiri et al, 2016;Carter & Be´langer, 2005;Hammad et al, 2019;Khasawneh et al, 2013;Kurfalı et al, 2017;Lallmahomed et al, 2017;Lin et al, 2011;Lu & Nguyen, 2016;Mensah et al, 2017Mensah et al, , 2018Mensah et al, , 2020Verkijika & De Wet, 2018;Zhao et al, 2019). In addition, considering the unique structure and cultural elements of each country, it is thought that every study made in this direction will contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The developing countries attempted to follow developed countries in their strategies and best practices regarding e-government implementation, but without local considerations; however, it ultimately resulted in massive IT/IS failures (Goldfinch, 2007;Heeks, 2006;Seetharaman, 2017;Pedersen, 2018;March;Hassan and Lee, 2019;Zahid and Haji Din, 2019;Hammad et al, 2019). The adoption of ICT and its use in the government sector faced different challenges mentioned in past research studies (Shah et al, 2011;Evans et al, 2019).…”
Section: Introductionmentioning
confidence: 99%